Synchronization of Chaos in Neural Systems - Nobukawa, Sou; Nishimura, Haruhiko (Frontiers in Applied Mathematics and Statistics, 2020)
Multiple non-linear systems demonstrate the phenomenon where fluctuations enhance the synchronization and periodic behaviors of systems. As the phenomenon induced by stochastic additive noise, in stochastic resonance, noise enhances the synchronization of system behaviors against weak input signals. Along with stochastic noise, deterministic chaos induces a phenomenon like stochastic resonance, called chaotic resonance. This review summarizes the progress of studies on chaotic resonance over the most recent decade. First, the fundamental characteristic of chaotic resonance was reviewed. Second, chaotic resonance in brain informatics, including cerebellar learning and deterministic fluctuations observed in electroencephalography/magnetoencephalography examinations, were reviewed. Third, the “reduced region of orbit” method was reviewed for the potential application of chaotic resonance. Through chaotic resonance, this review emphasizes the potential importance of recapturing neural fluctuation functionality, previously considered in the framework of stochastic resonance (also called stochastic facilitation), and assesses the effectiveness of applying chaotic resonance.